Characterisation of the membrane topology and molecular structure of LITAF to provide insights into the molecular pathogenesis of Charcot-Marie-Tooth disease type 1C. (25th February 2016) - Roberts, Rhys; Ho, Anita; Wagstaff, Jane; Garman, Elspeth; Freund, Stefan
Abstract: Background: The Charcot-Marie-Tooth (CMT) diseases are the commonest inherited neuromuscular disorders. These disorders are characterised by progressive degenerative peripheral neuropathies and are associated with mutations in over 80 genes. Mutations in LITAF cause CMT type 1C (CMT1C), an autosomal dominant demyelinating subtype of the disease. Why mutations in LITAF cause disease remains unclear, so we aimed to gather data about its molecular structure, which are lacking despite being highly conserved throughout evolution. Methods: We applied biochemical and cell biological techniques (differential membrane preparation, semi-permeabilisation and immunofluorescence microscopy, and cell-free protein expression) to determine the membrane topology of LITAF. Micro particle-induced X-ray emission (microPIXE) was used to establish whether LITAF associates with metal ions. We then analysed recombinantly expressed LITAF contructs by solution nuclear magnetic resonance (NMR) spectroscopy to gain structural insights to the LITAF protein, thereby allowing us to use the Rosetta software to generate a structural molecular model. Findings: We found that LITAF behaves as an integral membrane protein and that membrane association is dependent on six leucine residues found within the C-terminal LITAF domain. The membrane topology of the LITAF domain was such that both N-terminals and C-terminals were found on the cytosolic surface of endosomes and that these regions coordinated a single zinc atom. NMR spectroscopy was then used to characterise the secondary structural motifs of the LITAF domain, resulting in a correlation spectrum which was over 90% assigned. These data enabled us to create a structural model using NMR restraints and Rosetta. A LITAF construct harbouring a CMT1C-associated pathogenic mutation was then analysed by NMR, revealing marked structural shifts across the LITAF domain. Interpretation: We present the first structural model, to our knowledge, of the highly-conserved LITAF domain, which is a membrane-anchoring motif forming a zinc-binding structure on the surface of endosomes. We also show that a CMT1C-associated mutation causes large structural shifts across the LITAF domain, suggesting that structural instability on the surface of Scwann cell endosomes underpins the neuropathy seen in CMT1C. These insights will provide a platform for the development of future treatments. Funding: Wellcome Trust.